NaCl-salinity effect of on the growth and development of Chenopodium quinoa Willd plants - García, Miguel Angel; García Molano, José Francisco; Quito Martínez, Cristian Alfonso (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The salts have the ability to accumulate often in the soil of different crops, as a result of water and fertilizers used. A greenhouse experiment was carried out with the objective of studying the response of the vegetative phases of quinoa plants (Chenopodium quinoa Willd) at ascending concentrations of sodium chloride (NaCl). The seeds of quinoa variety Soracá were sown in bags with soil from the municipality of Ventaquemada (Colombia). The soil of the bags was gradually salified with NaCl by the addition of 0.0; 0.1; 0.2 and 0.3 M. days were measured to six and eight true leaves, days to branching and appearance of panicle; besides measuring length of stem, number of leaves, number of ramifications, content of chlorophyll, fresh and dry matter of root, leaves and stems and pH and electrical conductivity; observing that the plants presented significant statistical differences in the phenological development as well as in the height, number of branches and electrical conductivity, concluding that doses close to or higher than 0.3M generate the death of the plants, however electrical conductivities lower than 15, 2 dS.m-1 allows the plant to reach grain formation.